FAMÍLIAS DE ARANHAS DO CAMPUS DA UNIJUÍ, IJUÍ, RS - Silva, Lígia V. d.; Barros, Caroline R.; Kerpel, Bruno; Bruxel, Maciel; Pillatt, Naiara; Lopes, Tatiana; Quadros, Vanessa d.; Bianchi, Vidica (Salão do Conhecimento, 2013)
Resumo